2020
DOI: 10.3389/fmed.2020.00331
|View full text |Cite
|
Sign up to set email alerts
|

Selective Thyroid Hormone Receptor-Beta (TRβ) Agonists: New Perspectives for the Treatment of Metabolic and Neurodegenerative Disorders

Abstract: Thyroid hormones (THs) elicit significant effects on numerous physiological processes, such as growth, development, and metabolism. A lack of thyroid hormones is not compatible with normal health. Most THs effects are mediated by two different thyroid hormone receptor (TR) isoforms, namely TRα and TRβ, with the TRβ isoform known to be responsible for the main beneficial effects of TH on liver. In brain, despite the crucial role of TRα isoform in neuronal development, TRβ has been proposed to play a role in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
54
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(57 citation statements)
references
References 102 publications
(141 reference statements)
0
54
0
1
Order By: Relevance
“…On the other hand, although tafamidis does not seem to exhibit any other activity analog to hormonal molecules, thyromimetics have attracted attention for their therapeutic TH-like effects [ 29 , 30 , 31 , 32 ]. Diverse thyromimetics have been developed to modulate their activity, permeability, and selectivity, without hampering their therapeutic benefits [ 31 , 33 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, although tafamidis does not seem to exhibit any other activity analog to hormonal molecules, thyromimetics have attracted attention for their therapeutic TH-like effects [ 29 , 30 , 31 , 32 ]. Diverse thyromimetics have been developed to modulate their activity, permeability, and selectivity, without hampering their therapeutic benefits [ 31 , 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…Diverse thyromimetics have been developed to modulate their activity, permeability, and selectivity, without hampering their therapeutic benefits [ 31 , 33 ]. In particular, a series of thyromimetics specific for TH receptor β (TRβ) demonstrated various advantageous features against neurodegenerative diseases and metabolic disorders, without the severe side effects often mediated by the activation of TH receptor α [ 32 ]. One of the initial thyromimetics designed for this purpose is sobetirome (GC-1) [ 34 ], which exhibited most of the beneficial effects of T 3 against obesity and lipid metabolism disorder [ 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…These include the farnesoid X receptor agonists, obeticholic acid and cilofexor, as well as the peroxisome proliferator-activated receptor agonists, lanifibranor, pioglitazone, elafibranor, and seladelpar. Thyroid hormone receptors (THRs) represent the third class of nuclear receptors targeted for potential NASH therapy [8,9]. Endogenous thyroid hormones (THs), T4 and T3 (Fig 1A ), are important modulators of metabolic activity in mammals and alter cholesterol and fatty acid levels through binding and activation of THRs [10].…”
Section: Introductionmentioning
confidence: 99%
“…NSCs form a heterogeneous population, with the potential to give rise to both neurons and glial cells, depending on specific signals; for example, SVZ NSCs can generate oligodendroglial precursors (OPCs) after injury [ 175 , 204 ]. This latter effect is mediated by THs [ 226 , 227 ], and probably involves THRβ [ 227 ]. Based on this observation, it has been suggested that the use of THRβ agonists might be of help in the treatment of neurodegenerative disorders involving demyelination, such as multiple sclerosis [ 227 ].…”
Section: Thyroid Hormones and Mammalian Brain Developmentmentioning
confidence: 99%
“…This latter effect is mediated by THs [ 226 , 227 ], and probably involves THRβ [ 227 ]. Based on this observation, it has been suggested that the use of THRβ agonists might be of help in the treatment of neurodegenerative disorders involving demyelination, such as multiple sclerosis [ 227 ].…”
Section: Thyroid Hormones and Mammalian Brain Developmentmentioning
confidence: 99%